Dos posts e reposts dos Neabis Fortaleza e Paracuru à comunicação do IFCE no Instagram: o espaço das temáticas afro-brasileira e indígena - Silva, Saulo Rêgo da (2024)
The research investigates the space that Afro-Brazilian and Indigenous themes occupy in the communication of the Federal Institute of Ceará (IFCE) on Instagram through reposts of content made available on the Neabis profiles — the Neabis are the Afro-Brazilian and Indigenous Studies Centers. IFCE's own production is also considered. The institutional communication practices reflected in the official IFCE profiles on Instagram are read based on the concepts of integrated organizational communication by Kunsch (2003), focusing on the subarea of institutional communication, in a connection with public communication from the perspective of IFCE's activities through areas listed by Brandão (2009) and the adaptation of Kunsch's (2003) concepts by Holanda and Brandão (2019). The contents present in the Neabis profiles are read from the theoretical perspective of educommunication in the areas of media production, the formation of communication ecosystems and social struggles through authors such as Freire (1981, 1987); Kaplún (1998), Soares (2014) and Martín-Barbero (2014) and also through digital activism located in practices for the promotion of social and political causes that have the internet as an instrument of visibility, according to Ugarte (2008); Lemos (2003) and Milhomens (2009). Bülow (2020) remembers that they can involve people from individuals to groups. Within an economic, social and political structure of which racism is also part, as in the logic of biopower identified by Foucault (2002); of structural racism, according to concepts by Oliveira (2021) and Almeida (2018) and non-institutionalized racism, Sodré (2023), the Neabis' actions are in awakening needs that could go unnoticed, Kaplún (2017). The Neabis from two campuses (Fortaleza and Paracuru) were selected and, consequently, the Instagram profiles of the campuses linked to these Neabis, in addition to the general profile of IFCE. The analysis took place in posts in the feed and story spaces, in the months of April and November 2022. A predominance of reposts of institutional content was found in IFCE communication on Afro-Brazilian and Indigenous topics. This does not mean rejection of other themes, however, content that is promoted by Neabis themselves has a greater chance of repercussion. It was found that there is a predominance of content reposted, from external actors in the story space of the Instagram profile of the Neabis studied.